Visões dos formadores da licenciatura em matemática na construção dos saberes docentes - Haruna, Luiz Hiroaki [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
A presente investigação tem como objetivo buscar compreensões sobre as visões dos professores formadores da Licenciatura em Matemática a respeito da articulação da construção dos próprios saberes docentes com a atividade docente. A delimitação do campo de pesquisa deu-se após a realização de uma coleta de dados a partir de um questionário semi-estruturado dirigido a 12 (doze) professores, que ministram alguma disciplina ligada a Matemática. O trabalho insere-se em uma perspectiva qualitativa de investigação, buscando uma compreensão dos fenômenos estudados. Foram consultados documentos da Universidade, a legislação vigente e entrevistas. Buscou-se a utilização das teorias apresentadas pelos autores Tardif et al (1991), Shulman (1986) e Saviani (1996) sobre a tipologia dos saberes docentes. A análise indica que os formadores percebem a existência de tais saberes/conhecimentos, mas não o identificam claramente, além disso, com a atualização constante em conhecimentos ligados a Matemática, para o exercício da docência, percebem a necessidade dos conhecimentos disciplinares e não a existência de outros saberes/conhecimentos ligados à formação do futuro Professor de Matemática. É preciso concatenar as idéias dos atores envolvidos na formação assim como os objetivos que a Licenciatura deve atingir.

The aim of this work is to search for understanding the views of instructors in charge of the formation of prospective Mathematics teachers in graduate schools as far as the combination of teaching skills and the teaching activity itself is concerned. Fixing the boundaries of the research field was set after data collection based upon a semi-structured questionnaire answered by (12) twelve teachers who teach any subject related to Mathematics. The work fits into a qualitative perspective of investigation, seeking for understanding the phenomena studied. The University documents, the present legislation and interviews have been the sources of information. The theories of Tardif et al (1991), Shulman (1986) and Saviani (1996) about the tipology of teaching skills have been taking into consideration for the work to be based on. The analysis indicates that the instructors in charge of preparing future teachers, in spite of being aware of such skills and competence are unable to identify them clearly and besides that, make constant use only of the knowledge related specifically to Mathematics while teaching, thus accomplishing only the use of their competence in Mathematics ignoring the other skills and the knowledge connected to the formation of prospective Mathematics teachers that should be taken into consideration. It has been made necessary that not only the concepts of the instructors and all the staff directly involved in the process of formation, but also the objectives that the graduation is supposed to achieve, to be converged so as to provide the future Mathematics teachers with a holistic formation.
Keywords: Professores - Formação; Saberes profissionais; Prática docente; Ensino superior; Higher education